Perencanaan dan Perancangan Taman Budaya Aji Saka dengan Pendekatan Konsep Neo-Vernakular di Kabupaten Grobogan - Miarsono, Harry; Hetyorini, Hetyorini; Manalu, Tigor David; Roroyono, Arnida Dwi (Attractive : Innovative Education Journal, 2022)
Grobogan Regency is a Central Java regency with many cultures and arts. The absence of facilities accommodating crafts and cultural activities makes the community less aware. It does not preserve the existing Vernacular culture to maintain the culture and customs in Grobogan Regency. With these conditions, the problem formulation in this study discusses how the container for art and culture so that people are more directed and do not fall into negative associations—seeing the needs and potential of the planning and design of a cultural park to facilitate the community. The results of this study show that this cultural park is designed under the name Taman Budaya Aji Saka to commemorate the originator of Javanese script and uses the concept of Neo-Vernacular Architecture to maintain existing culture and customs and benefit the community as a supportive arts forum. Keywords: Grobogan Regency, Cultural Park, Aji Saka, Neo-Vernacular